2017
DOI: 10.1002/adfm.201605059
|View full text |Cite
|
Sign up to set email alerts
|

Elasticity, Flexibility, and Ideal Strength of Borophenes

Abstract: ABSTRACT:We study the mechanical properties of two-dimensional (2D) boron-borophenes -by first-principles calculations. The recently synthesized borophene with 1/6 concentration of hollow hexagons (HH) is shown to have in-plane modulus C up to 210 N/m and bending stiffness as low as D = 0.39 eV. Thus, its Foppl-von Karman number per unit area, defined as C/D, reaches 568 nm -2 , over twofold higher than graphene's value, establishing the borophene as one of the most flexible materials. Yet, the borophene has a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
203
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(209 citation statements)
references
References 66 publications
6
203
0
Order By: Relevance
“…The yielding strain is about 0.15 and 0.1 in the x and y directions respectively at the low temperature of 1 K. These values agree with ab initio results at 0 K283850. The yielding strain decreases with increasing temperature.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The yielding strain is about 0.15 and 0.1 in the x and y directions respectively at the low temperature of 1 K. These values agree with ab initio results at 0 K283850. The yielding strain decreases with increasing temperature.…”
Section: Resultssupporting
confidence: 87%
“…28, or 163 Nm −1 and 399 Nm −1 in ref. 50. Figure 9 shows that the Young’s modulus decreases with the increase of temperature.…”
Section: Resultsmentioning
confidence: 97%
“…Unlike conventional2Dn anomaterials, such as graphene, [32][33][34][35] borophenes, [36][37][38] silicene, [39][40][41] and black phosphorene, [42,43] MXenesh ave an extremely wide varietyo fc hemical composi-tions and structural arrangements at the atomic scale, [44,45] which endow them with many unique characteristics, including high electrical conductivity, plastic layer structure, small band gap, andl arge redox-active surfacea rea. [46][47][48] In spite of this, it remains ag reat challenge to fully utilize the advantages of MXenes because these unique traits and properties are highly related to the preparation processes that significantly influence their chemical compositions, layer structures,a nd surface functional groups.…”
Section: Synthesis Strategies and Propertiesmentioning
confidence: 99%
“…A lot of research has been devoted to studying outstanding properties of the borophene sheets in recent two years. It was observed that the borophene sheets are stiffer than the steel and unlike graphene, its mechanical ability is anisotropic and dependent on the * Izadi@webmail.guilan.ac.ir † m bagheri@guilan.ac.ir load direction [18,19]. In addition, same anisotropy has been reported for its electrical conductance that makes the borophene sheet an ideal candidate for electronic devices [20].…”
Section: Introductionmentioning
confidence: 82%